Karakterisasi Hidrologi dan Daur Limpasan Permukaan Daerah Aliran Sungai Ciliwung - Hidayat Pawitan; Naik Sinukaban (Jurnal Ilmu Pertanian Indonesia, 1991)
This research was done following the general water balance equation Pg - E* = R in three stages: preliminary, hydrometeorology, and runoff analyses. Measurements of infiltrations were conducted on the upper Ciliwung basin at different land units and cumulative basin infiltration was computed, and erosion was predicted using the USLE method. From the hydrometeorology analysis it was concluded that variations of  the point rainfall was diminishing in the downstream-to-upstream direction, however the opposite was true for the spatial distribution. Heavy rainfalls occurred at an average of five events in January and 0,2 events in July. The Average intensity varied between 8 mm and 20 mm/hr, and rainfall durations varied between 3 to 5 hours. Prediction of annual cumulative infiltration yielded 70 to 74 percent of total rainfall, and erosions exceeding the threshold levels of 20 to 43 ton/ha/yr only occurred in the uplands, shrubs, and plantations which are about 50 percent of the upper basin areal. Basin runoffs showed excessive ratios in many instances and at all time scales: hourly, daily, and monthly, ranging between 10 to 100 percent of total rainfall. It is considered due to contributions from groundwater sources which might not be limited to the basin boundaries. Time of concentrations also varied widely, i.e. 0.4 to 3.3 hours for upper, 0.9 to 7.1 hours fo middle, and 1.6 to 15.5 hours for lower outlets.